A MODEL OF STRATEGIC PLANNING FOR FINANCE MANAGEMENT OF MEDIUM-SIZED ENTERPRISES (SMES) IN INDONESIA - Arda Raditya Tantra; Ani, Dewi Ari; Dwi Jayanti, Fitri; Indarto, Bambang Ahmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to provide a strategic planning model in financial management for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to overcome problems in financial risk management. This study uses an interpretive approach through a systematic literature review of journals indexed by Scopus as a reputable international reference source, data collected from publications over two decades with a specific theme using PRISMA analysis which resulted in 152 articles. The findings show that MSMEs, especially medium-scale in Indonesia, are business entities with a large capacity to absorb labor. Although various MSME products have the potential to become high-quality export commodities, the process of managing financial risk effectively in the short term requires the implementation of the right strategy. Therefore, a strategic planning model is needed in MSME financial management to overcome these problems. Theoretically and practically, this systematically arranged model has the potential to be a successful and sustainable financial management solution for MSMEs in Indonesia, and can be implemented with field data related to MSME financial management. The novelty of this study lies in the focus of the discussion which specifically highlights the role of accounting in managing MSME financial risk in Indonesia.